Politics of Community Empowerment in the Development of Ketapanrame Tourism Village, Mojokerto Regency - Hidayatullah, Umar Ilham; Yuwanto; Fitriyah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This research examines the politics of community empowerment-based development in Ketapanrame Tourism Village, Trawas District, Mojokerto Regency. The main focus of the study is the analysis of the role of development actors, the impact of political empowerment, and the implications of the emergence of new elite capture in the development of tourist villages. A qualitative approach with a case study method was used to explore data through interviews, observation, and documentation. The results show that the development of Ketapanrame Tourism Village involves various community elements, such as local government, BUMDes, social groups, and economic groups that play a role in planning, implementing, and monitoring development. The impact of community empowerment includes financial, social, psychological, and political aspects. In addition, elite capture analysis reveals the potential for elite domination in managing development resources. This research contributes to the understanding of development politics at the local level by highlighting the importance of community participation in supporting the sustainability of tourism village development. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 10: Reduced InequalitiesSDG 11: Sustainable Cities and CommunitiesSDG 16: Peace, Justice, and Strong InstitutionsSDG 17: Partnerships for the Goals